NEW DIRECTIONS IN AGING: OLDER ADULTS AS EXPERTS AND INSTRUCTORS IN AN INTERGENERATIONAL UNIVERSITY COURSE ON AGING. (16th November 2018) - Nicholson, R; Spira, M
Abstract: New Directions In Aging is an intergenerational course co-designed and co-taught by senior living residents and a university instructor in which older adults educate university social work students about aging. Its aim is to challenge the stereotypes and false assumptions held by those with little direct contact with older people and to provide older adults the opportunity to share their lived expertise on topics that they consider of greatest importance. Class sessions centered on the lived experiences of the older adult co-instructors. Each resident teacher acted as lead discussant for 1–2 weeks and recounted a story from their life that would articulate their experiences relevant to the week's topic. During class, these stories were supplemented with questions and experiential exercises provided by the professor to facilitate conversation and provide opportunities for students and residents to break into small groups. Major themes from analysis of student interviews included the role of the course in dispelling aging-related stereotypes, growing student-instructor bonds and a corresponding increase in openness and shared vulnerability, and increased student comfort and capacity to discuss difficult topics. The main surprises for students were the resident-instructors' resilience and the fullness of resident-instructors' current lives. Students considered the most important topics covered by the course to be family dynamics/intergenerational conflict, spirituality and ageism/stereotypes about aging. A majority of students reported that the course had influenced their professional plans or how they worked with older adults. All students felt that this course was a unique, powerful complement to more typical lecture-based courses.